PERANAN PEMERINTAH DESA DALAM PEMBANGUNAN DESA RANTAU ASEM KECAMATAN KATINGAN KABUPATEN KATINGAN - Setyawan, Bayu; Benaya, Benaya; Berliana, Erla; Andani, Frima; Julinia, Julinia; Sawira, Sawira (JURNAL SOCIOPOLITICO, 2024)
This study aims to evaluate the role of the Rantau Asem Village Government in village development. A qualitative descriptive method was employed using observation, in-depth interviews, and literature review as data collection techniques. The study was grounded in role theory and the concept of village development. The Rantau Asem Village Government has fulfilled its role as an innovator by creating village development programs in an easily understandable language and encouraging community participation. exclamation As a motivator, the village government has fostered and maintained development dynamics by designing programs aligned with community aspirations. As a facilitator, the village government has facilitated the implementation of development projects and bridged various community interests. Nevertheless, there are still areas for improvement, such as enhancing human resource capabilities and skills. Additionally, the village government needs to adopt an appropriate approach to address community aspirations to boost community participation in village development.